A simple measure of the distributional burden of debt accumulation - Matt Jensen; Aspen Gorry (American Enterprise Institute (AEI), 2012)
Distributional analysis is an important feature in discussions of fiscal policy changes. While changes in taxes and spending are typically subject to distributional scoring, the distributional costs of changes in net debt are generally ignored. This paper proposes a measure of the distributional burden of servicing the debt. Our primary measure constructs the real annual cost of servicing the debt for households at various levels of income. The distributional burden of the debt depends critically on the level of interest rates and the manner in which the debt service is financed. Using alternative assumptions about financing, we assess the distributional burden of the current level of government debt and the burden of future debt projected to accumulate under current law, current policy, and the Administration's budget.
Keywords: H; 330; debt